Konstruksi Makna Keluarga Sakinah pada Pasangan Muslim Milenial: Kajian Sosiologi Keluarga dan Fiqh Munakahat - Ahmad Ass'ari; Dian Diyanti Putri (ISME : Journal of Islamic Studies and Multidisciplinary Research, 2025)
Social transformation, popular culture, and digital media developments have significantly reshaped how Indonesian Muslim millennial couples interpret the concept of sakinah family. The urgency of this study lies in the need to contextualize and reinterpret sakinah values in response to contemporary life dynamics. This research aims to explore the construction of sakinah meanings among Muslim millennial couples, focusing on shifts in family relational values, religious practices, and the influence of social media. Employing a qualitative method with a phenomenological approach, data were collected through semi-structured in-depth interviews with five urban Muslim couples selected by purposive sampling. Data were analyzed using thematic analysis based on social construction theory. The findings reveal that Muslim millennial couples perceive sakinah as a dialogical, egalitarian, flexible relationship characterized by emotional support, shaped through the interaction between religious doctrines, Islamic pop culture, and digital experiences on social media.